Frequency of biological non-skeletal materials in dry bone scenarios. (February 2021) - Biehler-Gomez, Lucie; Cappella, Annalisa; Mazzarelli, Debora; Cattaneo, Cristina
Abstract: In forensic anthropology, many small biological non-osseous materials may be found associated to skeletonized remains and can provide crucial information to the biological profile. Indeed, their careful recovery and correct identification can add information related to age-at-death, sex, ancestry, health, diet, migration and habits, and may be used in specific analysis such as DNA typing. However, and despite their potential, little is known about these non-osteological materials. Indeed, how frequent are they in dry bone cases? To answer this question, 100 skeletal remains with postmortem intervals ranging from 23 to 76 years from the CAL Milano Cemetery Skeletal Collection were meticulously examined for the presence of non-skeletal materials and in particular ossified cartilage, vascular calcifications, hair and nails. As a result, non-skeletal materials were found in 81 skeletal remains and showed high frequencies of recovery, despite the less-than-optimal conditions of exhumation of the skeletons. The high frequencies of non-skeletal materials obtained demonstrate the need for additional training and research given their informative power in forensic cases.